Aging process of black garlic using natural material as spontaneous fermentation medium - Satria Bhirawa Anoraga; Anjar Ruspita Sari; Iman Sabarisman; Jumeri Wikarta (Journal of Applied Food Technology, 2020)
This research aims to produce black garlic using various material such as clay chamber (kendil), bamboo chamber (besek), banana leaves, and aluminium foil. Single garlic var lanang (Allium sativum Var. Solo garlic) were cleaned up, weighed, covered by banana leaves, then put in clay chamber and bamboo chamber. Garlic were covered by alluminium foil used as control. All samples were aged using rice warmer in 60-70oC for 20 days. Brix(%) was measured using hand refractometer and antioxidant activity content was analyzed using 2, 2, diphenyl-1-picrylhydrazil (DPPH) assay. Result shows significant differences (P<0.05) on brix in obtained black garlic using clay chamber, bamboo chamber, and alluminium foil resulting a value of 5.2, 6.2 and 4˚Brix, respectively. Antioxidant activity content of black garlic were 60.5±0.156, 62,52±0,226 and 52.81±0.381% for clay chamber, bamboo chamber and alluminium foil, respectively, resulting the significant differences (P<0.05) among treatments. The antioxidant activity and brix of black garlic with bamboo chamber (besek) was significantly higher (P<0.05) than others. This result may provide beneficial information to home industry that produce black garlic for herbal food.